Efficacy of Cranberry Juice in the Prevention of Recurrent Urinary Tract Infection - Aziz, Uzma; Khan, Shazia Khalid; Altaf, Uzma; Zainab, Alia; Kanwal, Anikah; Naz, Farhat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the most common bacterial infections in primary care is urinary tract infections, which are second only to respiratory infections. Women are at higher risk of developing IBD. Cranberry has long been known for its beneficial effects on urinary tract health. Clinical trials have shown that regular consumption of cranberry juice can prevent UTI. Aim: To determine the efficacy of cranberry juice in prevention of recurrence of urinary tract infection in females with recurrent UTIs presenting in a tertiary care hospital. Study design& duration: Descriptive Case Series from 01-04-2016 to 30-09-2016. setting: Department of Obstetrics and Gynaecology, Jinnah Hospital, Lahore. Methods: A total of 160 females were prescribed 300mg concentrated cranberry extract twice daily for 12 weeks. Females were followed up in OPD at 6 weeks and 12 weeks for evaluation of symptoms and sign determined on clinical examination and a urine culture for recurrence of UTI, if symptoms of UTI and a +ve culture noticed during follow-up period then recurrence was labeled. Results: Patients ranged between 18-40 year. Mean age of the patients was 30.78±6.55 years. Total no of caseswas 160, 49 patients (30.6%) were primigravida and 111 patients (69.4%) were multigravida. Efficacy of cranberry extract was observed in 130 cases (81.3%). Stratification with regard to age, and parity was carried out Conclusion: In conclusion, the results of the present study support that cranberry extract associated with protective effect against recurrent urinary tract infections in our population.